CHALLENGES TO THE ACCOUNTING PROFESSION. - Zebley, John H. (The Accounting Review, 1956)
The author describes the challenges to the accounting profession in this article. He provides an insight to the background of accounting, the necessity of recording the terms of business transactions and the development of accounting techniques. He illustrates the increase in number of public accountants and the development of accounting as a profession with quotations as to the definitions of a profession. Discussing current challenges faced by the accounting profession he divides them into two categories which are the challenges within the profession and those initiated outside the profession. He further divides the outer challenges into two divisions which are, those which arise through technological changes in methods of recording and those which are enforced through the action of some who would take over certain segments. The author describes how more people can be encouraged to adopt the accounting profession and discusses questions related to certified public accountant certificate (CPA) examinations. He also describes the standards of education and experience for CPA candidates, the sphere of activities of a CPA and the formulation of accounting principles and standards of reporting.